Anterior Skull Base Sarcomas: Report of Characteristics and Outcomes at a Tertiary Care Cancer Center - Long, Sallie; Asimakopoulos, Panagiotis; McGill, Marlena; Cohen, Marc A.; Patel, Snehal G.; Shah, Jatin P.; Ganly, Ian (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective This study was aimed to describe our institutional experience on characteristics and treatment outcomes of sinonasal sarcomas invading the anterior skull base.Design Present study is a retrospective review.Setting The study was conducted at an academic cancer care center.Participants Thirty-one patients with skull base sarcomas treated with primary surgery from 1979 to 2015 were identified for this study from a preexisting database.Main Outcome Measures Survival and recurrence outcomes using the Kaplan–Meier method were the focus areas of the study.Results The median age was 44 years (range: 13–69 years). Twenty patients were male (64.5%). Twenty-nine patients underwent open craniofacial resection (93.5%) and two patients underwent endoscopic resection (6.5%). The majority of tumors were staged pT4 (77.4%). The most common pathologies were leiomyosarcoma (19.4%), osteosarcoma (16.1%), and chondrosarcoma (12.9%). Of those with known margin status, 10 patients had positive/close margins (32.2%) and 16 patients had negative margins (51.6%). Most tumors were high grade (74.2%). Twenty-three patients (74.2%) received adjuvant radiation and four patients (12.9%) received adjuvant chemotherapy. There were nine postoperative complications (29%) including one mortality and three cerebrospinal fluid leaks. There were 10 local, 2 regional, and 5 distant recurrences over a median follow-up of 74 months (range: 1–300 months). The 5-year disease-specific survival (DSS) was 69.8%. The 5-year locoregional recurrence-free probability (RFP) was 63.2% and the 10-year distant RFP was 71.7%. The 5-year DSS for high grade tumors was 64.2 and 85.7% for low grade tumors (p = 0.117).Conclusion This study contributes an updated analysis of anterior skull base sarcomas. Five-year DSS is approximately 70%. Analysis of survival outcomes based on grade, tumor size, and other factors is limited by small sample size and the rarity of these tumors.
Keywords: head and neck sarcoma; skull base sarcoma; paranasal sarcoma; sarcoma outcomes